Nurse-patient communication using ICT: a scoping review - Marlene Peres; Raquel Simões de Almeida; António Moreira (Instituto Politécnico de Viseu, 2024)
Introduction: Technology is revolutionizing diagnoses, treatments, and other procedures, offering constant innovations that promote healthcare efficiency and quality. Objective: Explore how nurses use information and communication technologies (ICT) to communicate with patients, uncover challenges in these interactions, and identify their needs. Methods: The scoping review methodology allowed us to identify studies encompassing three databases: LILACS, ScienceDirect, and PubMed. The systematic search strategy included Portuguese and English language articles published between 2014 and 2024 that were then screened and assessed for inclusion. A narrative synthesis was used to integrate and report the findings. Results: The analysis of the ten studies yielded five key findings: 1) the use of ICTs in nurse-patient communication; 2) enhanced communication skills; 3) perceived benefits; 4) challenges encountered; and 5) needs. It is evident that patient communication positively impacts health and is a valuable strategy to address the rising demand for healthcare services. Conclusion: These findings highlight communication skills that promote evidence-based practices and are required by professionals in an aging society and a totally digital and technologically dependent world. Specific training programs related to the development of effective communication skills by nurses with patients using ICT should be considered by nursing schools and health institutions.